Pengaruh Fraksi Etanol Dalam Pelarut Dan Ketebalan Coating TiO2 Terhadap Kinerja Prototip Dye-Sensitized Solar Cell (DSSC) berbasis Dye Dari Buah Tumbuhan Senduduk (Melastoma malabathricum) - Haq, Arinil; Amri, Amun; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The globally encountered energy crisis can be solved by utilizing sunlight as an alternative energy source. Sun energy can be harnessed through application on solar cell. Dye-sensitized solar cell (DSSC) is a type of solar cell which utilizes dye as light-harvester and also assensitizer. This research aims to investigate the usage of malabar melastome (Melastoma malabathricum) as dye material and to observe the impact of ethanol solvent’s dilution and coating thickness of TiO2 on the DSSC’s performance. To fabricate the DSSC, material preparation and dye extraction was done by dissolving fruit of malabar melastome in amixture of 40 ml ethanol, 8 ml acetic acid, and 52 ml aquadest. The making of TiO2 paste was done by mixing 5 g of TiO2 with 40 ml solvent and deposited using spin coating method. Themaking of electrolyte was done by dissolving 0,127 g of iodine in 0,5 M of KI solvent. The counter-electrode was made and the DSSC was assembled. The DSSC’s voltage was thenexamined using multitester and analyzed using SEM, UV-Vis spectrophotometry, and adhesion test. The higher ethanol fraction in the solvent and the thicker the coating of TiO2,the better voltage resulted. This fact is supported by the morphology and adhesivity test. It can be proved from the highest voltage that is obtained from the sample with 100% ethanol fraction and the thickness of 240 μm which is 659 mV/cm2 under the illumination of LEDlight and 1806,7 mV/cm2 when applied on direct sunlight.Keywords: DSSC, photovoltaic, malabar melastome, spin coating, TiO2